STRATEGI PIMPINAN DALAM MENANGANI KRISIS PASCA PENYALAHGUNAAN KEKUASAAN KARYAWAN DI PT. OSJAS - Nur'rahma; Zainuddin, Sumarni; Suriady, Israwaty (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2019)
The research objectives are (1) To determine the stage of the crisis that occurred at PT. OSJAS, (2) To describe the leadership strategy in dealing with the crisis after the abuse of power of employees at PT. OSJAS. This type of research is a qualitative research with a case study basis. This research was conducted at PT. OSJAS which is located in Tawaili District, North Palu. The research concept is about the crisis and the leadership strategy in dealing with the crisis at PT. OSJAS, subjects or informants in this study amounted to seven people. The type of data used in this study is the type of primary and secondary data. As a tool in data collection using observation and in-depth interviews (depth interviews). The results showed that the crisis faced by PT. OSJAS is a stage of Crisis Resolution. This stage of crisis resolution was obtained in accordance with the results of the study by identifying the crisis that the problems that arise are caused by the abuse of power of employees who are given special authority as managers of PT. OSJAS. PT. OSJAS is in the resolution stage because it has gone through the repair process. Furthermore, in the incident the leadership of PT. OSJAS handled the crisis with an adaptive strategy with quite extensive handling steps. The first was to change the policy by dismissing SA as a manager at PT. OSJAS to avoid even greater losses, the second to straighten the company's image, this strategy is to restore public trust in the company from negative perceptions by delivering information related to the case that occurred at PT. OSJAS.